DESIGN OF PILOT PLANT TO OBTAIN SILVER USING A CLOSED CYLINDRICAL ELECTRODEPOSITION SYSTEM (Professional paper) (Nexo Revista Científica, 2018)
Artisanal mining companies are characterized by a deficient plant design for the implementation of current and/or alternative mineral extraction processes; this is why it was designed and implemented a pilot plant for obtaining silver using an ecofriendly system of electrodeposition. The plant prototype is divided into four sections: The first, preparation of mineral, corresponds the unit of crushing and the milling unit of the ore; the second, leaching and Filtering section comprises the solution preparation, leaching and filtration units; the third section electrodeposition, comprises a unit of electrodeposition; and finally the casting section containing the cathode drying unit and the casting unit. With the alternative process to implement, is that the process of obtaining tailings that will be used for the production of fertilizer.